Utilization of cassava peel waste (Manihot esculenta) as substrate in the production of cellulase enzymes by Aspergillus niger - Hendriantika, Ratu Dewi; Peristiwati; Surtikanti, RR. Hertien Koosbandiah (Universitas Muhammadiyah Surakarta, 2026)
Cellulase enzymes is an enzyme that can hydrolyze cellulose into smaller sugar components. Cellulase enzymes are produced due to high demand, with 29.17% in the animal feed industry, 14.67% in the textile industry, and 26.17% in the paper industry. One method of producing cellulase enzymes is by utilizing the cellulolytic microorganism Aspergillus niger. This study aims to optimize cellulase enzyme production by Aspergillus niger through liquid fermentation on cassava peel substrate (Manihot esculenta) with pH treatments of 4.5 and 5.5 and temperatures of 29.5 and 30.5℃. The research method involved isolating pure cultures of Aspergillus niger from the laboratory of PT. Agritama Sinergi Inovasi. The fungus was grown on CMC agar medium to test its cellulolytic activity. The tested cellulolytic fungus can be used in fermentation in a medium containing cassava peel powder as the main cellulose substrate. The results of this study indicate that the cellulolytic fungus Aspergillus niger has the potential to produce cellulase enzymes. The highest enzyme activity value of 2.003 U/mL with a biomass of 0.535 mg/mL was obtained at pH 4.5 and 30.5℃. This study provides an important contribution in assessing the potential for cellulase enzyme production with variations in pH and temperature by Aspergillus niger fungi on cassava peel substrate as a basis for further development in organic waste management.